PENGARUH TINGKAT PENGANGGURAN TERHADAP INFLASI DI KOTA SURABAYA - M IQBAL SURYA P (Jurnal Pendidikan Ekonomi (JUPE), 2013)
This study examines the effect of the unemployment rate to the inflation in the city of Surabaya in 1998-2011. The purpose of this study was to determine whether the unemployment rate affect inflation and also to forecast the unemployment rate and inflation until 2020. Analysis techniques used are vector autoregressive analysis techniques (var). From the analysis it can be concluded that the unemployment rate had no significant effect on inflation in the city of Surabaya. addition to the results of analysis also showed the state of inflation for 2013 and 2014 are 7.3% and 2014 up to 2020 was 7.2%, while unemployment in the year 2013 to 2020 amounted to 8.6 to 8.8 %. Keyword: unemployment, inflation